Radio and the rise of the Nazis in prewar Germany - Maja Adena; Ruben Enikolopov; Maria Petrova; Veronica Santarosa; Ekaterina Zhuravskaya (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
How do the media affect public support for democratic institutions in a fragile democracy? What role do they play in a dictatorial regime? We study these questions in the context of Germany of the 1920s and 1930s. During the democratic period, when the Weimar government introduced progovernment political news, the growth of Nazi popularity slowed down in areas with access to radio. This effect was reversed during the campaign for the last competitive election as a result of the pro- Nazi radio broadcast following Hitler's appointment as German chancellor. During the consolidation of dictatorship, radio propaganda helped the Nazis to enroll new party members. After the Nazis established their rule, radio propaganda incited anti-Semitic acts and denunciations of Jews to authorities by ordinary Germans. The effect of anti-Semitic propaganda varied depending on the listeners' predispositions toward the message. Nazi radio was most effective in places where anti- Semitism was historically high and had a negative effect in places with historically low anti-Semitism. – – Inwieweit können die Medien zum Schutz oder zur Untergrabung ungefestigter Demokratien beitragen? Und inwieweit können sie Unterstützung für die Politik des Diktators generieren? Wir analysieren diese Fragen im Kontext des Radios in der Weimarer Republik und dem frühen NSRegime. In der Zeit zwischen 1929 und 1932, in der das Rundfunkprogramm pro-demokratisch ausgerichtet war, hatte das Radio einen signifikant negativen Einfluss auf die Wahlergebnisse der NSDAP. Dieser Effekt wurde bereits 5 Wochen nach der Ernennung Hitlers zum Kanzler und der Kontrollübernahme über das Rundfunkprogramm umgekehrt. Nachdem die Nazis ihre Macht konsolidiert hatten, trug die Rundfunkpropaganda messbar zu vermehrten Parteieintritten und zur Zustimmung der Bevölkerung bei der Denunziation von Juden und zu anderen Formen des offenen Antisemitismus bei. Dennoch war der Einfluss der NS-Propaganda nicht uniform. Je nach Voreingenommenheit der Zuhörer konnte die Propaganda sehr effektiv oder aber kontraproduktiv sein. Das NS-Radio war am effektivsten in Orten mit historisch hohem Antisemitismus und hatte einen negativen Effekt auf die Unterstützung der antisemitischen Politik in Orten mit historisch niedrigem Antisemitismus.
Keywords: D72; L82; N74; 330; Anti-semitism; dictatorship; media; Nazis; propaganda; unconsolidated democracy